Strategic behaviour and decision making in competitive hospital markets: an experimental investigation - Johann Han; Nadja Kairies-Schwarz; Markus Vomhof (International Journal of Health Economics and Management, 2024)
Abstract We investigate quality provision and the occurrence of strategic behaviour in competitive hospital markets where providers are assumed to be semi-altruistic towards patients. For this, we employ a laboratory experiment with a hospital market framing. Subjects decide on the quality levels for one of three competing hospitals respectively. We vary the organizational aspect of whether quality decisions within hospitals are made by individuals or teams. Realized monetary patient benefits go to real patients outside the lab. In both settings, we find that degrees of cooperation quickly converge towards negative values, implying absence of collusion and patient centred or competitive quality choices. Moreover, hospitals treat quality as a strategic complement and adjust their quality choice in the same direction as their competitors. The response magnitude for team markets is weaker; this is driven by non-cooperative or altruistic teams, which tend to set levels of quality that are strategically independent.
Additional information: C92;D03;D43;D64;I11;L13
Keywords: 330; Quality competition; Hospital markets; Team decisions; Altruism; Laboratory experiment